The praxis of stupidity: an explanation to understand the barriers mitigating rework in construction - Love, Peter; Smith, J.; Ackermann, Fran; Irani, Z. (Taylor & Francis, 2018)
The practice of ‘functional stupidity’ forms the essence of Alvesson and Spicer’s ‘Stupidity-based theory of organisations’. Functional stupidity is an incapacity and/or disinclination on the part of organisational members to exercise critical reflection about what they are doing, to understand why they are doing it, and determine what the consequences of their activities are beyond the immediate task at hand. Drawing on the authors’ empirical research with regard to the nature of rework causation, we have observed that there is a proclivity for functional stupidity to reside in everyday practice in construction. We noticed that functional stupidity was a recurring organisational issue explicitly linked to ‘power and politics’ that was played out in numerous construction projects. In these projects managers attempted to discourage critical reflection that called into question prevailing organisational norms and values that had been sanctioned under the auspices of a ‘zero-vision’. In some instances, this, in turn, led to reinforcing ‘stupidity self-management’ behaviour whereby employees intentionally limited their own critical reflection creating a vicious zone of zemblanity that kept being played out in projects. The corollaries in this instance being an inability to learn, engender innovation, and improve organisational and project performance.